Impulse Buying Behavior of Mahasantri at IAIN Ponorogo in the Context of Shopee Periodic Promotions in the Perspective of Islamic Consumption Ethics - Fiska Amelia Kartika; Muhtadin Amri; Mayrina Eka Prasetyo Budi; Azhira Fitria Rahmawati; Adamu Abubakar Muhammad (Niqosiya: Journal of Economics and Business Research, 2025)
Introduction: Impulse buying behavior is increasingly widespread, especially in the context of Shopee periodic promotions among mahasantri, sometimes it is not in accordance with consumption ethics in Islam. That way, this research was compiled which aims to find out and analyze how impulse buying behavior in the context of Shopee periodic promotions from the perspective of Islamic consumption ethics, and what are the motivations and impacts of this behavior. This research uses qualitative research methods with a descriptive approach. Based on the results of the analysis, among IAIN Ponorogo students, there are several types of impulse buying, namely Planned Impulse buying, Pure Impulse buying, and Suggestion Impulse buying, while Reminder Impulse buying occurs but with a very low frequency. In an Islamic perspective, consumption activities should be based on ethical principles, but some mahasantri tend to deviate from this principle by doing impulse buying that is excessive, unplanned, and driven by momentary desires. The motivation for impulse buying behavior in students at IAIN Ponorogo is influenced by social needs, the need to increase self-esteem and self-actualization, and perceptions of decision making. Impulse buying behavior has an impact on the finances, lifestyle, and psychology of the students at IAIN Ponorogo. In terms of finance, spending becomes uncontrollable because of the temptation to buy from Shopee.